2016
DOI: 10.1007/s00167-016-4137-7
|View full text |Cite
|
Sign up to set email alerts
|

Injury patterns and risk factors for orthopaedic trauma from snowboarding and skiing: a national perspective

Abstract: Prognostic Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 56 publications
8
25
2
1
Order By: Relevance
“…However, this study provides a precise diagnosis of each patient analysed in this study instead of injury registration through retrospective interviews with skiers or medical staff. Particularized injuries cannot be differentiated because of coding limitations in the registration system [38]. Also, the results of the present study only showed that injury patterns differ between sexes.…”
Section: Discussioncontrasting
confidence: 77%
“…However, this study provides a precise diagnosis of each patient analysed in this study instead of injury registration through retrospective interviews with skiers or medical staff. Particularized injuries cannot be differentiated because of coding limitations in the registration system [38]. Also, the results of the present study only showed that injury patterns differ between sexes.…”
Section: Discussioncontrasting
confidence: 77%
“…Idzikowski et al (13) surveyed injuries from 47 medical facilities near Colorado ski resorts and showed that of 7,430 snowboarding-related injuries, 3,645 (49.06%) were upper extremity injuries and 56.43% of these were fractures. Moreover, several studies have reported that wrist injuries were the most common type of injury associated with snowboarding (5,15). Kim et al (5) collected injury data from 1988 to 2006 from a base-lodge clinic in Vermont and found that wrist injuries accounted for 27.6% of all snowboarding injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (5) collected injury data from 1988 to 2006 from a base-lodge clinic in Vermont and found that wrist injuries accounted for 27.6% of all snowboarding injuries. In another study, Basques et al (15) used the National Trauma Data Bank and identified 2,704 snowboarders who presented to EDs between 2011 and 2012, and found that most common injuries were upper extremity fractures, which accounted for 26% of injuries, particularly of the distal radius, which accounted for 10.5% of injuries. Machold et al (16) surveyed a group of snowboarders who had a mean age of 15 years, and found that 6% of snowboarders had a mean of 10.6 injuries per 1,000 snowboard days, where 61% of the injuries affected the upper extremity, particularly the wrist, which accounted for 32% of the injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The most common fracture types were simple extra-articular (A2) and simple intra-articular (C1), representing 36.8 and 27.0% of radius fractures in this population. Using the National Trauma Data Bank, Basgues et al determined that distal radius fractures are more prevalent in snowboarders relative to skiers (10.5% of all presenting injuries vs 2.7%) [23]. Others have found a similar pattern, with distal radius fractures representing 2.2% of injuries in skiers and 14.5-17.4% in snowboarders [16,24].…”
Section: Epidemiology Of Distal Radius Fractures In Athletesmentioning
confidence: 99%